2020
DOI: 10.1126/sciadv.abd4998
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based estimates of decline and rebound in China’s CO 2 emissions during COVID-19 pandemic

Abstract: Changes in CO2 emissions during the COVID-19 pandemic have been estimated from indicators on activities like transportation and electricity generation. Here, we instead use satellite observations together with bottom-up information to track the daily dynamics of CO2 emissions during the pandemic. Unlike activity data, our observation-based analysis deploys independent measurement of pollutant concentrations in the atmosphere to correct misrepresentation in the bottom-up data and can provide more detailed insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 58 publications
10
104
0
1
Order By: Relevance
“…These findings, which are consistent with other recent studies (e.g. Zeng et al, 2020), are not unexpected. Regional XCO 2 enhancements due to fossil fuel emissions are typically only 1 to 2 ppm and even a 10 % emission reduction would therefore only correspond to a reduction of the fossil-fuel-related regional XCO 2 enhancement by 0.1 to 0.2 ppm.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings, which are consistent with other recent studies (e.g. Zeng et al, 2020), are not unexpected. Regional XCO 2 enhancements due to fossil fuel emissions are typically only 1 to 2 ppm and even a 10 % emission reduction would therefore only correspond to a reduction of the fossil-fuel-related regional XCO 2 enhancement by 0.1 to 0.2 ppm.…”
Section: Discussionsupporting
confidence: 94%
“…They concluded that these places have not been well observed by the OCO-2 satellite because of frequent or persistent cloud conditions and they give recommendations for future carbon-monitoring systems. Zeng et al (2020) used modelling, GOSAT XCO 2 and other data sets. They conclude that GOSAT is able to detect a short-term global mean XCO 2 anomaly decrease of 0.2-0.3 ppm after temporal averaging (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in XCO 2 growth, as estimated from the target-background difference, reveals that the related atmospheric concentration changes can be detected by column measurement from the satellite; however, the method is too simplified to quantify the reduction in anthropogenic emission. The reduction is a bit higher than the average reduction in China (11.5%) inferred by sector-specific ratio maps of CO 2 to NOx emissions, where the latter was estimated from TROPOMI NO 2 reduction [17]. These estimations are higher than the bottom-up estimation (6.6%) from the traffic data in Beijing [18] or the average reduction in China estimated from all inventories (~10%).…”
Section: Xco 2 Anomaly From Gosatmentioning
confidence: 60%
“…The variations in human CO 2 emissions have been considerable within just a few months, but, depending on both their human origin and the specific local development of the pandemic, have been concentrated in some places that changed over time. In early April, emissions in China rebounded to pre‐pandemic levels (Zheng, Geng, et al, 2020) as several Western countries had only started restrictions on mobility. Within the same country, Covid‐induced emission reductions could coexist with an increase in emissions linked or not to the pandemic: according to the National Bureau of Statistics of China (http://data.stats.gov.cn/english/), thermal power generation in some western provinces of China (Yunnan, Xinjiang, and Guangxi) notably increased in March, while it decreased in the eastern provinces of China.…”
Section: Conclusion and Discussionmentioning
confidence: 99%